OVEREXPRESSION OF MsDNAJ-PROTEIN ENHANCES DROUGHT TOLERANCE IN TRANSGENIC TOBACCO PLANTS - Ki-Won Lee; Md. Atikur Rahman; Hee Chung Ji; Ki-Yong Kim; Hyung Soo Park; Gi Jun Choi; Sang-Hoon Lee (Journal of Animal and Plant Sciences, 2019)
As a co-chaperone DNAJ proteins play pivotal role in abiotic stress responses in plants, but the biological functions of DNAJ are poorly documented. In order to reveal the function of MsDNAJ proteins, physiological and molecular responses were investigated using transgenic tobacco plants. In this study, we showed that the transcript level of transgene MsDNAJ was elevated under drought treatment. The ectopic expression of MsDNAJ transgenic tobacco exhibited lower malondialdehyde (MDA) and hydrogen peroxide (H2O2) under drought condition. Moreover, the transgenic plants showed better growth with high chlorophyll fluoresce (Fv/Fm) and proline content compared to wild type (WT). In addition, overexpression of MsDNAJ improved drought stress tolerance in transgenic plants. These results suggest that overexpression of tobacco MsDNAJ protein gene enhanced drought tolerance in transgenic tobacco plants.
Keywords: MsDNAJ; Drought stress; Tolerance; Transgenic tobacco